Framework for enhancement of image guided surgery: finding area of tumor volume - Hameed, Shihab A.; Aboaba, Abdulfattah A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Daoud, Jamal Ibrahim; Saeed, Rashid Abdelhaleem; Mahmoud, Omer (INSI Publications, 2012)

(untitled)
The advantages offered by Image Guided Surgery (IGS) to medical professionals during a minimally-invasive surgical operation are overwhelming. Although a sophistication growth in imaging techniques can provide the surgeon with high quality guidance but there is still a need for more improvement in IGS application such as: computational time which impedes its full deployment in intra-operative surgical interventional, segmentation, registration, visualization, IGS application software and instrumentation. This paper presents a model for a more effective computational scheme by looking at possible computational improvement at all stages of IGS procedure but focusing on two aspects of IGS relating to intra-operative surgical intervention. The implementation of such improvement will result into fast and better anatomical segmentation and fast computational scheme. The other problem discussed in this paper is to find a suitable method to determine the tumor volume in an accurate way that will help surgeon to remove it precisely.